Development of the Organizational and Economic Mechanisms of Greenhouse Industry in the Republic of Uzbekistan - DURMANOV, Akmal; UMAROV, Sukhrob; RAKHIMOVA, Khavakhon; KHODJIMUKHAMEDOVA, Shakhida; AKHMEDOV, Azamat; MIRZAYEV, Shakir (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
The goal of the article is to analyse the improvement of the organizational and economic mechanisms of the glasshouse industry in the Republic of Uzbekistan. The following methods were used in the study: comparative analysis, statistical method, estimation method, economic analysis of the results. Results of the study: the use in the greenhouses of the Republic of Uzbekistan of innovative new generation greenhouses with energy-saving technologies will reduce energy consumption, save resources and reduce the cost of vegetables. The scientific importance is the development of innovative technologies in agriculture in the Republic of Uzbekistan, and the practical importance is ensuring the efficiency of agricultural development.